Regimen Kemoterapi Pasien Kanker Payudara di RS Santo Borromeus Bandung - artha utami (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Breast cancer is the highest type of cancer suffered by women in Indonesia and the highest cause of death. Complicated chemotherapy management if not given properly can reduce efficacy and increase side effects. Therefore, this study aims to look at the description of the chemotherapy regimen in breast cancer patients undergoing chemotherapy at the Santo Borromeus Hospital Bandung in January – December 2021. This research is a descriptive study with a survey design. The subject of this study was breast cancer undergoing chemotherapy at the Santo Borromeus Hospital in the period January – December 2021, which found 57 patients. The sampling technique used in this research is saturated sampling. Most breast cancer patients at Borromeus Hospital are 45-55 years old (40.35%), and have stage III (40.35%). Patients who showed positive HER-2 were 33.33%. The single most widely used regimen was transtuzumab (24.56%). The most widely used combination regimen was a regimen containing taxane (43.84%).